Comparative Genomics Reveals Evolutionary Traits, Mating Strategies, and Pathogenicity-Related Genes Variation of Botryosphaeriaceae - Yu, Chengming; Diao, Yufei; Lu, Quan; Zhao, Jiaping; Cui, Shengnan; Xiong, Xiong; Lu, Anna; Zhang, Xingyao; Liu, Huixiang (Frontiers in Microbiology, 2022)
Botryosphaeriaceae, as a major family of the largest class of kingdom fungi Dothideomycetes, encompasses phytopathogens, saprobes, and endophytes. Many members of this family are opportunistic phytopathogens with a wide host range and worldwide geographical distribution, and can infect many economically important plants, including food crops and raw material plants for biofuel production. To date, however, little is known about the family evolutionary characterization, mating strategies, and pathogenicity-related genes variation from a comparative genome perspective. Here, we conducted a large-scale whole-genome comparison of 271 Dothideomycetes, including 19 species in Botryosphaeriaceae. The comparative genome analysis provided a clear classification of Botryosphaeriaceae in Dothideomycetes and indicated that the evolution of lifestyle within Dothideomycetes underwent 4 major transitions from non-phytopathogenic to phytopathogenic. Mating strategies analysis demonstrated that at least 3 transitions were found within Botryosphaeriaceae from heterothallism to homothallism. Additionally, pathogenicity-related genes contents in different genera varied greatly, indicative of genus-lineage expansion within Botryosphaeriaceae. These findings shed new light on evolutionary traits, mating strategies and pathogenicity-related genes variation of Botryosphaeriaceae.